Quality Test of Student Worksheets Based on Contextual Teaching And Learning for Class XI High School Physics - Desnita Desnita; Amali Putra; Sadra Hamida; Putri Bullquis Marsa; Dira Novisya (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to produce teaching materials in the form of CTL-based worksheets for class XI at Senior High School. The method used in this research is the method of development. The initial stage is an analysis of the teaching materials used by teachers at school. Before being tested on class XI students, the worksheets were validated by experts as well as physics teachers and students at Senior High School 1 Gunung Tuleh. After being validated, improvements were made according to the suggestions given. The average results of the validation of learning experts, physicists, and linguists were 0.77, 0.90, and 0.81 from all aspects. The practical value of teachers and students is 79.68 and 87.43 with the valid category. After testing the validity and practicality of the physics learning videos, the results of the effectiveness test of the learning videos were obtained to measure students' critical and creative thinking skills. The average N-gain values are 0.22 and 0.26. With the overall results obtained, it can be concluded that the contextual-based worksheets that have been developed are suitable for use in learning activities